An Adapted Procedure for Calibration of the Non-digital Peak Pressure Indicators: Motor Compression Measuring Devices - Ekici, C. (METROLOGY SOC INDIA, 2017)
This paper is written for proposing a guideline to calibrate non-digital peak pressure gages. Motor compression testers are peak pressure measuring devices. Accuracy tests were applied to the motor compression testers and the accuracy classes of the devices were found in the study. These accuracy classes were used to select calibration procedure according to Euramet's Guidelines on the Calibration of Electromechanical Manometers and Euramet's procedure was adapted to calibration of non-digital peak pressure measuring devices. About seventy devices were tested in this study to find their accuracy classes. Measurement uncertainty budgets and the adapted procedure were given in this study.
Keywords: Motometer; Pressure calibration; Peak pressure indicators; Motor compression testing devices; STANDARD; STABILITY; MPA; Instruments & Instrumentation; Physics